Hospitalization Trends for Acute Kidney Injury in Kidney Transplant Recipients in the United States, 2004–2014. Issue 11 (November 2019) - Garg, Neetika; Kumar, Nilay; Singh, Tripti; Parajuli, Sandesh; Astor, Brad C.; Mandelbrot, Didier; Djamali, Arjang
Abstract : Background: The incidence of acute kidney injury (AKI) and AKI requiring dialysis (AKI-D) in the general population is increasing. However, there is limited information on the epidemiology of AKI-related hospitalizations in the prevalent US kidney transplant population. Methods: We analyzed trends in the incidence of hospitalizations with primary diagnosis of AKI and secondary diagnosis of AKI and AKI-D using data from the National Inpatient Sample 2004–2014. Co-primary endpoints were in-hospital mortality, length of stay (LOS), and cost. Survey analysis techniques were used to compute national estimates. Linear trends in outcomes were evaluated using linear regression. Results: There were a total of 37 562 hospitalizations for primary AKI, 136 628 for secondary AKI, and 10 731 for AKI-D during the study period. We found an increase in hospitalizations for all 3 diagnoses over time (13.7–24.7 per thousand kidney transplant recipients [KTRs] for primary AKI, 37.4–108.0 per thousand KTRs for secondary AKI, and 4.2–6.0 per thousand KTRs for AKI-D; all P trend < 0.01). This was accompanied by significant improvements in in-hospital mortality (3.2%–0.5% for primary and 6.1%–4.4% for secondary AKI; both P trend < 0.01), average LOS (5.3–4.6 days for primary and 8.4–7.2 days for secondary AKI; both P trend < 0.001), and cost (11 635–8234 for primary and 21 373–17 470 for secondary AKI; P trend < 0.001 for both). Conclusions: The incidence of hospitalizations for AKI and AKI-D among KTRs is rapidly rising. This has been accompanied by significant improvements in in-hospital mortality, LOS, and cost. Abstract : Supplemental Digital Content is available in the text.